(untitled) (REMUNOM, 2026)
The ketogenic diet (KD) has gained prominence as an effective nutritional and therapeutic approach for managing various clinical conditions, including refractory epilepsy, obesity, type 2 diabetes, and neurodegenerative diseases. However, the limited availability of ready-to-eat products with appropriate ketogenic profiles poses a challenge to dietary adherence. In this context, avocado stands out as a promising ingredient due to its high content of monounsaturated fats, fiber, and bioactive compounds. This study aimed to develop and characterize two avocado-based paste formulations for ketogenic diets, focusing on centesimal composition, physicochemical properties, and microbiological safety. Two formulations were prepared: F1 (with coconut milk and oil) and F2 (with coconut milk, oil, and cocoa), which underwent physicochemical analysis according to Instituto Adolfo Lutz (2008) protocols and microbiological evaluation based on ANVISA’s Normative Instruction No. 161/2022. The results showed that both formulations had high lipid content (F1: 11.93%; F2: 11.53%) and low carbohydrate content (F1: 8.68%; F2: 8.04%), consistent with the nutritional requirements of a ketogenic diet. The total energy value was high in both samples, while protein levels were moderate. Microbiological analyses confirmed that the products met the safety standards for consumption. Therefore, the developed formulations are nutritionally suitable, microbiologically safe, and present potential for incorporation into the functional food market targeted at low-carbohydrate dietary patterns.